Congo Red Staining: An Effective Affordable Tool For Diagnosis Of Bovine Leptospirosis - Shyma V. H; Bipin K. C; Deepa P. M; Tresamol P. V; Ambily R; Ratish R. L; Dinesh P. T (The Indian Veterinary Journal, 2025)
The present study involves evaluation of dark field microscopy and Congo red staining of urine sediments for diagnosis of leptospirosis in clinically suspected cases. A total of 24 urine samples were collected from cattle with clinical signs viz; hematuria, jaundice, hemagalctia and abortion. Mid stream urine samples were collected in sterile containers and transported immediately to laboratory. Smears were prepared from urine sediments and air dried. Methanol fixed smears were stained with 1% Congo red solution and observed under 100X magnification. Negatively stained leptospires could be observed in two cases. These samples were later confirmed with polymerase chain reaction. Hence congo red staining can be used as a low cost diagnostic tool for leptospirosis.